Integrity among academics: concept, challenge and way forward - Alias, Bity Salwana; Ishak, Mohd Radzi; Mansor, Azlin Norhanni; Mohamad Nasri, Nurfaradila; Zainudin, Zaida Nor (Scientific Research Publishing, 2019)
The degree of integrity among academics is yet to be determined because there is no proper instrument for such measurement. The purpose of this paper is therefore to identify elements that can measure integrity, as well as develop integrity framework or model. Among the themes discussed in this paper are, what are the theories, models and concepts related to integrity, previous studies on integrity and subsequent discussions on the development process of the model that are appropriate for measuring integrity. This concept paper concludes that integrity can be measured based on the values required for integrity. The implication of this concept paper is that the values that are inherent in a person determine their level of integrity. This concept paper recommends that integrity should be measured over time. It is not only to produce an index of integrity but also to remind academics of the appropriate values and practices in fulfilling their responsibilities. Furthermore, ongoing exposures to integrity instruments may prevent misconceptions about integrity that only associated with corruption, abuse of power, unprofessional and inaccurate matters in terms of duties, responsibilities, roles or positions held.